Implementation of Taukil Wali at the KUA of Jati District, Kudus Regency from the Perspective of Minister of Religious Affairs Regulation Number 20 of 2019 - Zahro, Almadatus Saekhatus; Rahma, Nabila Luthvita (Nurani, 2023)
The role of the guardian in marriage is an important pillar that must be fulfilled. In the event that the guardian is unable to attend the ceremony, representation can be made by the Head of the Sub-district KUA or Penghulu. The practice of "taukil wali" in Jati Sub-district is quite common, sometimes for justifiable reasons and sometimes without valid reasons. This research aims to explore the implementation of "taukil wali" in the KUA of Jati Sub-district in accordance with the Regulation of the Minister of Religious Affairs Number 20 of 2019. This research takes a Juridical Empirical approach, involving fieldwork to collect data on the application of "taukil wali" in the jurisdiction of KUA Jati, analyzed based on PMA Number 20 of 2019. The findings show that the application of "taukil wali" in KUA Jati is in accordance with the regulation. However, there are consequences that must be considered if the appointed guardian is not valid. Among them is the potential annulment of the marriage, which results in the absence of legal rights and obligations for the parties involved and the possibility of legal action. Even if the nasab guardian does not know the condition of the prospective bride, taukil wali is still carried out using taukil wali bil kitabah, in accordance with the provisions of PMA Number 20 of 2019.